Height as Related to Self-Perceived Mate Value and Attractiveness - Fernandez-Tapia, A (American Psychological Association Inc., 2019)
A study among 66 couples from Santiago, Chile examined the association between objectively assessed height and self-reports of mate value and attractiveness. In addition, assortative mating for these variables was assessed. There was some evidence for assortative mating: Although there was no correlation between the height of both partners, there were significant correlations for attractiveness and mate value. Men were taller than women, but there was no evidence for the male-taller norm. Among women, mate value and especially attractiveness were higher as they were taller, with a slight dip in mate value among women of medium height. Among men, only attractiveness was higher as they were taller. Discrepancies and similarities with previous research are discussed. © 2018 American Psychological Association.
Keywords: height; posture; mate value; attractiveness